Processing methodology for regional AEM surveys and local implications. Issue 1 (2nd January 2020) - Reninger, Pierre-Alexandre; Martelet, Guillaume; Perrin, José; Dumont, Marc
ABSTRACT: Airborne Electromagnetic (AEM) data are increasingly used in many geoscientific applications. BRGM conducted regional AEM surveys on the French overseas volcanic islands, where issues, including groundwater management or risk assessment are crucial. For such "infrastructural" surveys, the data are intended to be used for various purposes and over several years. In this type of environment, with a man-made imprint, a complex geology and rugged topography, the data processing can be very challenging. We therefore developed and implemented an original reprocessing method for regional AEM datasets. It aims to optimise, at a study scale, the coverage, the lateral and vertical resolution and the depth of investigation compared to more "standard" processing. This is highlighted through three examples. Our method includes regional processing procedures on both navigation and EM data: calculation of the effective tilt of the instrument frame, use of a DGPS-derived altitude, application of the singular value decomposition filtering and stacking with an adaptive trapezoid filter. Moreover, a local tuning of the inversion and manual editing are achieved for each study.